Chromophoric signatures of microbial by‐products in the dark ocean. Issue 14 (30th July 2016) - Catalá, Teresa S.; Reche, Isabel; Ramón, Cintia L.; López‐Sanz, Àngel; Álvarez, Marta; Calvo, Eva; Álvarez‐Salgado, Xosé A.
Abstract: Detailed examination of the absorption spectra from dark ocean samples allowed us to identify and deconvolve two distinct chromophores centered at 302 nm (UV) and 415 nm (visible) from the exponential decay curve characteristic of humic substances. The UV chromophore was ubiquitous in intermediate and deep waters, and it has been proposed as the secondary absorption peak of nitrate. The visible chromophore was prominent at the central and intermediate water masses of the North Pacific, and it has been proposed as cytochrome c. Subtraction of the modeled absorption spectra of the two chromophores from the measured absorption spectrum of the samples leads to a spectral slope overestimation by 13.3 ± 6.0% for S 275–295 and 14.8 ± 10.6% for S 350–400 . To only consider the chromophoric fraction of DOM, the absorption spectra of nitrate should be subtracted in samples with a [NO3− ]: a 302 ratio > 70 µ M m. Key Points: Two distinct chromophores have been detected in the dark global ocean A chromophore centered at 302 nm is due to the secondary absorption peak of nitrate A chromophore centered at 415 nm is presumably due to cytochrome c and can be a used as proxy for cumulative respiration